2nd International Conference on Creative Multimedia 2022 (ICCM 2022) 2022
DOI: 10.2991/978-2-494069-57-2_21
|View full text |Cite
|
Sign up to set email alerts
|

Online Game-Based Learning to Enhance Student Engagement, Motivation and 21st-Century Skills

Abstract: In the year 2020 Covid-19 pandemic became a global health concern with significant educational implications. Stay-at-home orders have been issued by governments worldwide, resulting in the closure of institutions and universities. Thereby, educators had to conduct their classes online to ensure educational continuity. However, some of the significant challenges of poorly designed online learning environments were low student involvement in the online classes, which led to the deficit of collaboration, engageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…The higher completion rate for GBQAs compared to Moodle-based learning suggests that game-based learning was more engaging for students. Additionally, the higher average completion rate indicates that students were more actively involved in the game, which aligns with the findings of previous studies (e.g., [20,29,62]). Furthermore, students accessed game-based activities more frequently than MBQAs, which could be for entertainment purposes or to improve their scores for self-satisfaction.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The higher completion rate for GBQAs compared to Moodle-based learning suggests that game-based learning was more engaging for students. Additionally, the higher average completion rate indicates that students were more actively involved in the game, which aligns with the findings of previous studies (e.g., [20,29,62]). Furthermore, students accessed game-based activities more frequently than MBQAs, which could be for entertainment purposes or to improve their scores for self-satisfaction.…”
Section: Discussionsupporting
confidence: 89%
“…Many pieces of research have shown that most people enjoy playing games, and this enjoyment can lead to an increase in engagement and motivation during educational activities [29]. The concept of gamification has gained extensive attention in recent years as a possible way to make learning more enjoyable and engaging.…”
Section: Literature Reviewmentioning
confidence: 99%